Kesetaraan Gender dalam Pendidikan Islam Perspektif M. Quraish Shihab - Luqman Hakim (Pustaka Peradaban, 2023)
Gender equality and women’s emancipation have remained intriguing topics over the past decade, spanning a spectrum of discussions from the academic sphere to religious scholars, and even the general public. In reality, women continue to face discrimination, stereotypes, and subordination across various facets of life. Women have not yet achieved an equal footing with men when it comes to taking on public roles, particularly within the realm of education. Paradoxically, Islamic civilization has witnessed the presence of remarkable women figures who have made substantial contributions in religious, educational, economic, and socio-cultural domains. M. Quraish Shihab, an intellectual and Islamic scholar, as well as a distinguished professor in the field of Quranic exegesis, has demonstrated significant concern for gender equality and the role of women. Employing the methodology of library research, this research article seeks to delve into M. Quraish Shihab’s thoughts on gender equality, through his work in the interpretation of Al-Misbah and numerous other scholarly works related to the subject matter. The article concludes that Quraish Shihab provides a lucid portrayal by interpreting Quranic verses regarding women and gender equality issues based on his multifaceted approach to interpretation, which offers diverse interpretations relevant to societal contexts. Quraish Shihab successfully constructs a vision of gender equality within the framework of Islamic values to eradicate all forms of discrimination against women, encompassing aspects of household, marriage, societal interactions, and particularly education. Isu kesetaraan gender dan emansipasi wanita dalam dekade akhir ini masih menjadi perbincangan yang menarik di berbagai kalangan, mulai dari kalangan akademisi, Ulama, hingga masyarakat umum. Realitas menujukkan bahwa kaum wanita masih banyak mendapatkan perlakuan diskriminatif, steorotipe, dan tersubordinasi dalam berbagai aspek kehidupan. Wanita belum mendapatkan ruang yang sama layaknya pria dalam mengambil peran publik, terutama dalam pendidikan. Padahal dalam peradaban Islam telah banyak tokoh wanita hebat yang memiliki andil besar dalam bidang agama, pendidikan, ekonomi, serta sosial-kultural. M. Quraish Shihab merupakan Intelektual-Ulama sekaligus guru besar bidang tafsir Al-Qur’an yang menaruh perhatian besar terhadap isu kesetaraan gender dan peran wanita. Melalui metode penelitian library research, artikel penelitian ini berusaha mengupas pemikiran M. Quraish Shihab tentang kesetaraan gender dan wanita melalui tafsirnya Al-Misbah dan banyak karya ilmiah lainnya yang berkaitan. Tulisan Ini menyimpulkan bahwa Quraish Shihab memberikan gambaran yang jelas dengan menafsirkan ayat-ayat Al-Qur’an tentang wanita dan isu-isu kesetaraan gender berdasarkan corak penafsirannya yang memiliki beragam interpretasi yang relevan dengan kondisi masyarakat. Quraish Shihab berhasil membangun visi kesetaraan gender dalam bingkai nilai-nilai Islam untuk mengikis segala bentuk diskriminasi terhadap wanita, baik dalam bidang rumah tangga, pernikahan, sosial masyarakat, terutamanya dalam hal pendidikan.